Eligiendo Escuelas: English Learners and Access to School Choice. (September 2017) - Mavrogordato, Madeline; Harris, Julie
School choice has emerged as the linchpin of President Trump's urban education reform plan, but it remains unclear how school choice policies will shape the educational experiences of the most underserved student groups, particularly English learners (ELs). Using quantitative data from one large urban school district, we examine EL participation in a system of school choice. Specifically, we investigate the extent to which never, current, and former ELs enroll in a nonzoned school. We find significant differences in the likelihood that students across these groups engage in school choice, raising important questions about whether school choice reforms are accessible to current ELs.